Meaningful learning on polymers from experimentation and problematization - Graziane Gomes dos Santos; Tiago Nery Ribeiro; Divanizia do Nascimento Souza (Amazônia, 2018)
The aim of this study was to investigate on the learning of students in senior high school chemistry classes during activities related to the subject polymers in a didactic sequence (SD). We decided to explore the data from a qualitative type approach, employing some aspects of discursive textual analysis, based on experimental activities. The students participating in the research formed two groups, one from a private school and another from a public school. First, the students' prior knowledge on the subject was investigated, based on Meaningful Learning Theory. Then, the activities of the didactic sequence (DS) were developed and the students’ discourses were analyzed based on the answers to questions. The strategies used were motivating and served as advanced organizers for the subsuming concepts. As the subsuming concepts became more elaborate, the students were able to understand new information and learn significantly. In this context, we can consider that the activities of DS related to the concepts about polymers already existing in the student's cognitive structure.